2010
DOI: 10.1186/1471-2407-10-613
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in regulatory regions of Cyclooxygenase-2 gene and breast cancer risk in Brazilians: a case-control study

Abstract: BackgroundCyclooxygenase-2 (COX-2) is up-regulated in several types of cancer, and it is hypothesized that COX-2 expression may be genetically influenced. Here, we evaluate the association between single-nucleotide polymorphisms (SNPs) in the COX-2 gene (PTGS2) and the occurrence of breast cancer among Brazilian women.MethodsThe study was conducted prospectively in two steps: First, we screened the promoter region and three fragments of the 3'-untranslated region of PTGS2 from 67 healthy Brazilians to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
33
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 56 publications
6
33
0
Order By: Relevance
“…Genetic variations in the 8473T>C polymorphisms of COX-2 gene may contribute to increased stability of mRNA and the synthesis of COX-2 (Piranda et al, 2010). Researchers from Cox et al have reported three separate studies in the American population to test the hypothesis that polymorphisms in COX-2 are associated with BC risk (Cox et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic variations in the 8473T>C polymorphisms of COX-2 gene may contribute to increased stability of mRNA and the synthesis of COX-2 (Piranda et al, 2010). Researchers from Cox et al have reported three separate studies in the American population to test the hypothesis that polymorphisms in COX-2 are associated with BC risk (Cox et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…(Gallicchio et al, 2006;Langsenlehner et al, 2006;Cox et al, 2007;Vogel et al, 2007;Brasky et al, 2011), 2 of Asians group (Gao et al, 2007;Gao et al, 2014), and 3 of other groups (2 Mixed and 1 African) (Shen et al, 2006;Piranda et al, 2010;Fawzy et al, 2013). Among 12 studies in this article, 10 studies were performed in PCC study (Gallicchio et al, 2006;Langsenlehner et al, 2006;Shen et al, 2006;Cox et al, 2007;Vogel et al, 2007;Piranda et al, 2010;Brasky et al, 2011;Festa-Vasconcellos et al, 2012) and 2 in HCC study (Gao et al, 2007;Gao et al, 2014). In addition, genotype and allele distribution for each study were summarized in Table 2.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…We found that the C allele occurs at a frequency of 20.6% in the GC patients. A high percentage of C allele had been observed among Portuguese (19) , Brazilian (21) , and Dutch patients (25) (22%, 32% and 41%, respectively). Studies on European and American populations have reported a higher prevalence of C allele than studies involving Asian (2,4,10) .…”
Section: Discussionmentioning
confidence: 99%
“…Since the identification of the COX-2 -765G>C polymorphism (18) , studies have shown a correlation between this polymorphism and different types of cancer (3,21,25,30) . In this study we observed the frequency of the COX-2 -765 G/G, GC and CC genotypes were 59%, 34% and 7% in GC patients were similar to those previously reported by Pereira et al (19) for a Portuguese population (49%, 44% and 7%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decade, numerous molecular epidemiological case-control studies have been conducted in diverse ethnic backgrounds to explore the association between the COX2 -765G>C polymorphism and risks of various cancers, including breast cancer (Piranda et al, 2010), colorectal carcinoma (Daraei et al, 2012), esophageal (Bye et al, 2011) and gastric cancers , hepatocellular carcinoma (He et al, 2012), leukemia (Zheng et al, 2011), lung cancer (Coskunpinar et al, 2011), lymphoma (Monroy et al, 2011), ovarian (Agachan Cakmakoglu et al, 2011, head and neck (Peters et al, 2009), pancreatic (Zhao et al, 2009), skin (Cocoş et al, 2012), and cervical cancers (Pandey et al, 2010), among others. However, due to the relatively small sample sizes, the results obtained from these studies have been inconclusive or even controversial.…”
Section: Introductionmentioning
confidence: 99%